A Comparative Study Between Antioxidant Potential of Ripe and Pre-ripe Mango Using Conventional and Physiological Extraction. Issue 1 (2nd January 2016) - Bhatt, Anjali; Patel, Vinayak
ABSTRACT: Mango is distinctive among all fruits considering its exceptional flavors. All varieties of mango have their unique essence. It is one of the largest consumed fruits worldwide. Its antioxidant properties are also well known due to the presence of carotenoids and phenolic compounds. Unlike other studies, this study considers that the methanolic extraction may not well reflect the antioxidant activity of mango after consumption, i.e., in vivo. Thus, an in vitro gastrointestinal model has been used for the simulation of digestion of pre-ripe and ripe mango samples. Both samples thus extracted are compared with their conventional methanolic extracts for their antioxidant compounds and antioxidant activity. Interesting differences in the two types of extracts can be observed. The simulated gastrointestinal extracts show significantly higher antioxidant properties in parameters, such as total phenol content, flavonoid content, flavonol content, carotenoid content, reducing power, and radical scavenging activity. From the results, it can be concluded that the conventional extracts under rate the antioxidant value of mangoes and they may have much higher health significance than they are believed to have.